The Diagnosis of Brain Death - Gritsenko, S. M. (Transplantation and artificial organs, 2021)
Organ transplantation is impossible without donation which is performed both intra vitam and posthumously. Each case of multi-organ collection provides help to 4 to 6 patients. We believe that presentation of modern algorithms for diagnosing brain death is quite feasible, and such information can be useful not only for anesthesiologists, but also for doctors of other specialties. This paper presents materials related to organ donation. Diagnostic criteria for human brain death, as well as the procedure for ascertaining human brain death and the actions of doctors of healthcare institutions in relation to persons who are in these institutions and who have clinical indications for the diagnosis of brain death, are determined by "The procedure for cancellation of active measures to maintain the patient’s life…". Active measures (ventilation, infusion therapy and vasopressor support, etc.) to support the patient’s life are cancelled after the patient’s brain death is ascertained, except for cases where the deceased person is considered a potential donor. Verification of the human brain death is carried out by the case management team of the healthcare institution involving, if necessary, members of consultative and diagnostic mobile team, specialists of other healthcare institutions. The head of the healthcare institution is responsible for timely and proper engagement and work of the case management team. The responsible person determines the membership of the case management team by making an appropriate entry in the case record and is responsible for its work. An anesthesiologist and a neurologist (neurosurgeon) who have at least 5 years of practical experience in the specialty are engaged in the case management team to ascertain brain death in persons over 18 years of age. Physicians involved in the removal of human anatomical materials and transplantation thereof, as well as transplant coordinator, may not be included in the case management team.